2022
DOI: 10.1007/s12665-022-10531-5
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of groundwater vulnerability assessment methods in a rapidly urbanizing city: evidence from Dakar, Senegal

Abstract: In rapidly growing cities in the tropics, unregulated urban development presents a major risk to groundwater quality. Here, we assess the vulnerability of an unconfined aquifer of Quaternary sands in the Thiaroye area of Dakar (Senegal) to contamination using four GIS-based indices (DRASTIC, DRASTIC_N, SINTACS, SI). Our correlation of assessed vulnerability to observed impact is semi-quantitative, relating observed groundwater quality, based on nitrate concentrations and tryptophan-like fluorescence to vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Dakar, the capital of Senegal, is a rapidly expanding metropolitan city in sub-Saharan Africa [1]. Consequently, the rapid urban sprawl of Dakar has resulted in the expansion of the Thiès region, situated 70 km away from Dakar.…”
Section: Socio-economic Factors Influencing Forested Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Dakar, the capital of Senegal, is a rapidly expanding metropolitan city in sub-Saharan Africa [1]. Consequently, the rapid urban sprawl of Dakar has resulted in the expansion of the Thiès region, situated 70 km away from Dakar.…”
Section: Socio-economic Factors Influencing Forested Areasmentioning
confidence: 99%
“…In recent years, concerns regarding the decline in forest resources have been investigated. According to the literature, unregulated urban development poses a significant risk to groundwater quality [1] and exerts critical pressure on natural resources. Moreover, changes in the functioning of the Earth's ecological systems present a significant threat to human survival [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the Thiaroye aquifer, measured nitrate concentrations rapidly increased over the last decades mainly caused by the expansion of unplanned urbanization and the infiltration of domestic wastewater into the groundwater due the poor sanitation system in the peri-urban areas. Nitrate values in Thiaroye aquifer varies between 5 to 34 mg·L −1 between 1966 and 1972 and presently reach an average of 400 to 450 mg·L −1 (Diédhiou et al, 2011;Diouf et al, 2012;Diaw et al, 2020;Pouye et al, 2022).…”
Section: Drinking Water Qualitymentioning
confidence: 99%
“…Many approaches have been developed to evaluate aquifer vulnerability. They include process-based methods, statistical methods, and overlay and index methods (Pouye et al, 2022;Kirlas et al, 2022;Eynakware et al 2022c and d;Kalinski et al (1993) and Eke (2017) opined that the basis of index-based integrated electrical conductivity is that the vertical travel time of water through a set of geological layers can be related to the resistivity properties of these layers, which implies that, the method (which is based on the principle that the distribution of electrical potential in the subsurface around current-carrying electrodes) depends on the electrical resistivity. Oli et al (2022) demonstrated that the protection degree of an aquifer or vulnerability may be considered directly proportional to the longitudinal conductance (LC) of the overburden materials.…”
Section: Introductionmentioning
confidence: 99%